“In the time to denounce”: the political conjuncture of 1930 and the writings of the common prisoners of the Recife House of Detention (Tempo e Argumento, 2025)
This article investigates several writings by ordinary prisoners written in the Casa de Detenção do Recife in the context of the 1930 Revolution. We intend to scrutinize the positive correlations between the political context external to the prison and the emergence of these manuscripts, as well as examine their claims in order to reveal a sophisticated process of appropriating the political rhetoric propagated by the Liberal Alliance in the context of its mobilization. Diverging from the usual approaches by not focusing on the actions of political prisoners, we investigated the connections and porosities between the internal dynamics of the prison and the external political turmoil, highlighting a political and associative dimension in the petitionary practice of ordinary prisoners, subjects overlooked by traditional approaches to the history of prisons in the Age Vargas. To this end, we mobilize a diverse documentary typology (official letters, requests, habeas corpus, letters, petitions, newspapers, opinions from the Penitentiary Council, reports and “daily parts”) with the aim of overcoming the repeated and predominant use of the memories of political prisoners as a source exclusively to investigate the daily life of prisons at this juncture.
Keywords: House of Detention; common prisoners; newspapers; appropriation